Development of Laser-Induced Fluorescence Detection Devices for Astrobiological and Planetary Science Applications - Duca, Zachary A. (Georgia Institute of Technology, 2021)
Microcapillary electrophoresis (µCE) enables high-resolution separations in miniaturized, automated microfluidic devices. Pairing this powerful separation technique with laser-induced fluorescence (LIF) enables highly-sensitive, quantitative, and compositional analysis of organic molecule monomers and short polymers, which are essential, ubiquitous components of life on Earth. Improving methods for their detection has applications to multiple scientific fields, particularly those related to medicine, industry, and space science. This research focuses on the latter of these fields through advancement of organic molecule detection techniques for biosignature detection missions to celestial bodies within our Solar System, such as Europa. Plume activity and evidence supporting a global subsurface ocean have made Europa a high-priority target for future NASA outer-planetary missions. In situ quantitative and compositional analysis of organic molecules in the plumes or subsurface ocean of Europa would provide relevant, detailed information on formation, habitability, and on-going planetary processes of these celestial bodies and could provide the first evidence of the potential for extant life beyond Earth. A modular benchtop microcapillary electrophoresis with laser-induced fluorescence (µCE-LIF) detection system was constructed and tested by analyzing standard amino acid samples of valine, serine, alanine, glycine, glutamic acid, and aspartic acid in multiple borate buffered solutions of increasing concentrations from 10-50 millimolar (mM), all pH 9. The 35 mM borate buffer solution generated the highest resolution before Joule heating dominated. The limits of detection (LODs) of alanine and glycine using 35 mM borate buffer were found to be 2.12 nanomolar (nM) and 2.91 nM, respectively, comparable to other state-of-the-art µCE-LIF instruments using a spectrometer as a detector. Furthermore, the microdevice is easily exchanged to fit the desired application of the system and optical components within the central filter cube can be easily replaced to target alternative fluorescent dyes. Using the benchtop µCE-LIF detection system, high-resolution separations of an amino acid standard solution, including valine, serine, alanine, glycine, glutamic acid, and aspartic acid, contained within icy moon analogue solutions of sulfuric acid, carbonic acid, sodium carbonate, and magnesium sulfate were obtained. Separations were improved by diluting the salts in solution, regulating the pH, and sequestering cations with ethylenediaminetetraacetic acid (EDTA). Using these methods, an icy moon (Enceladus/Europa) analogue sample taken from Champagne Geyser at Chaffin Ranch in Utah was analyzed for amino acids and found to contain leucine, valine, serine, alanine, and glycine by direct comparison to spiked standards. Alanine and glycine were quantified via standard curve at 80.1 ± 0.8 µM and 900 ± 100 nM, respectively, while leucine, valine, serine, and glycine again were quantified at 4.4 ± 0.8 µM, 830 ± 80 nM, 780 ± 60 nM, and 1.0 ± 0.2 µM, respectively. To begin developing the µCE-LIF technique for an outer-planetary mission setting, a pneumatically-actuated monolithic membrane microdevice fabricated in 2005 was functionally tested after 10 years of storage under ambient conditions. Using a square wave with a 500 millisecond (ms) actuation pulse width and a 1000 ms period and operating under vacuum at -980 millibar (mbar) from ambient pressure, all microvalves opened in less than 1 hour. The vacuum required to actuate an open valve ranged from -218 to -175 mbar from ambient pressure. The microvalves were then programmed to transfer fluid through the microdevice for flow rate characterization. Fluidic transfer occurred at a flow rate of 122 ± 8 microliters/minute (µL/min) right-side up in Earth’s gravitational field and 110 ± 10 µL/min upside down in Earth’s gravitational field. These results addressed (1) a concern that these systems may have a limited shelf-life and (2) a concern that performance depends specific device orientation in a gravitational field, indicating likely successful implementation in an orbital microgravity environment after an extended period in storage. To further develop the µCE-LIF technique for an outer-planetary mission setting, the effect of drying 10+-year-old Pacific Blue (PB) dye with amino acids was examined by performing a set of three experiments: a liquid control where every solution was mixed normally in its liquid form, a partial-liquid control where each solution was dried using a spin vacuum and resuspended to mix before adding liquid PB, and a dry test where each solution was dried using a spin vacuum and resuspended to mix after adding dry PB. The partial-liquid control showed a similar signal-to-noise (S/N) intensity when compared to the liquid control, while S/N of the organics for the dry test displayed a reduction in intensity. However, statistical analysis revealed that only the aspartic acid dry test was significantly different than the liquid and partial-liquid controls. A likely cause of this decreased signal for aspartic acid was the hydrolysis of PB. A 2x excess of PB when stored with amino acids would alleviate any potential loss in S/N. These results indicate that PB dye can retain sufficient reactivity when stored dry with amino acid standards. To minimize mass, size, and power, a portable lens tube LIF detection prototype was developed to quantify bulk organics in a liquid sample. A limit of detection (LOD) analysis was performed by reacting various concentrations of leucine with fluorescamine dye in 35 mM borate buffer, pH 8.5. The LOD was found to be 11.8 µM, an excellent benchmark for a prototype LIF detection system of its unique design. Automated analyses were performed using a fast-prototyped microfluidic processor and showed no statistically-significant differences when compared to the manual analyses. A sample (Y31B) collected from the Atacama Desert in Yungay, Chile, was analyzed manually and found to contain 300 ± 50 µM of bulk amines. When analyzed using the automated microfluidic processor, the sample was found to contain statistically equivalent 289 ± 4 µM of bulk amines. These results show the promise of using automated microdevices and portable lens tube LIF detection systems in more restricting environments, like those on Europa and Enceladus. Quantitative, compositional, and chiral analysis of small organic molecules in situ provides important information for studying planetary formation and evolution, and, more excitingly, also can provide signatures of past or present life. MicroCE-LIF detection is a unique technique currently ready for further development for space flight that has the resolution, selectivity, and sensitivity to provide these analyses. While lander or fly-by missions have largely been the focus for the development of µCE-LIF, as proposed in the Mars Organic Analyzer (MOA) and Enceladus Organic Analyzer (EOA), there has been limited development of LIF detection systems for more extreme environments, like the surfaces of the icy moons Europa and Enceladus. This demonstration that microdevices retain full functionality after over 10 years of storage, the successful separation and detection of organic molecules contained within an icy moon analogue sample using a µCE-LIF benchtop system, and the quantification of organics in a planetary analogue sample using a miniaturized lens tube LIF detection system represent a significant step forward for the liquid-based analysis of small organic molecules and biopolymers for future space missions to icy bodies like Europa and Enceladus. Ph.D.